Mylabris (Mylabris) snizeki sp. nov. from Jordan, with a key to the Jordanian species of the nominotypical subgenus (Coleoptera: Meloidae) - Černý, Ladislav; Vrabec, Vladimír (Zootaxa, 2019)
Mylabris (Mylabris) snizeki sp. nov. from Jordan is described and an identification key to Jordanian species of the nominotypical subgenus is provided.